Ajax and REST Recipes - Gross, Christian (Apress, 2012)
This book focuses on practical solutions for implementing Ajax, JavaScript, and Representational State Transfer (REST)–based Web services and functionality. I want to promote the development of applications that are decoupled (client code is separate from the server code), applications that can be adequately tested and maintained, and code that can be used by clients outside of the Ajax context. I believe in Ajax, but I also believe that if you can develop Ajax code that non-Ajax clients can access, then your application has a distinct advantage over others.